The Scar Boys : a novel - Vlahos, Len (Egmont USA, 2014)
Written as a college admission essay, eighteen-year-old Harry Jones recounts a childhood defined by the hideous scars he hid behind, and how forming a band brought self-confidence, friendship, and his first kiss.